UNDERLYING SCHOOL DROPOUTS ISSUES IN SARAWAK - Dolly, Paul Carlo; Athirah, Azhar; Tharshini, Sivabalan (UNIMAS Publisher, 2024)
Students who leave school without completing formal education still remain an issue in Malaysia. This study is based on the research tracing the journey of school dropouts in Sarawak, Malaysia and the focus of this paper is identify the issues behind it. A cross-sectional survey was used to complete the data collection process among 120 school dropouts selected through purposive sampling. The obtained data were analysed using Statistical Package for the Social Sciences (SPSS), described in frequency and cross-tabulated. The study discloses that most of the school dropouts come from the suburban areas (69.2%) compared to urban areas (30.8%). More males (54.2%) than females (45.8%) dropped out of school and most dropped out at secondary (77.5%) compared to primary (22.5%) school level. Interestingly, the number of students who dropped out from the academic schools (96.7%) is higher than those from the technical school (3.3%). More females than males got married at the schooling age of 18 years old and below. What is thought-provoking on these findings are issues underlying the school dropouts such as the lack of opportunity and social inequality, quality of education, inadequate facilities and infrastructures to facilitate students to continue and complete their education. These issues should be taken into seriously. It is not just the economic concerns of poverty and unemployment but there is also a need to include structural and social concerns such as inequality and violation of children’s right. The underlying background of those who are still in school need to be addressed and studied by all the stakeholders involved and they should be sensitive to their backgrounds in order to identify relevant measures to prevent those who are at risk from further dropping out of school.